RETURN TO PLAY: Where are we going? It is not a guessing game - Pruna, R. (Apunts Medicina de l'Esport, 2016)
Return to play is one of the most important key points within the recovery process of the injured player. It is essential to understand the RTP as a constant decision making process. RTP has to be understood as a dynamic and personalised process. The main objective has to be the absence of further re-injuries but not to exactly predict the RTP time.